2019
DOI: 10.1063/1.5121442
|View full text |Cite
|
Sign up to set email alerts
|

Microwave heating and spark plasma sintering as non-conventional synthesis methods to access thermoelectric and magnetic materials

Abstract: The development of new—cheaper, more efficient, more sustainable, and more reliable—functional materials with useful properties calls for ever-improving, smart, and innovative synthesis strategies. A multitude of inorganic compounds are already used as energy materials, i.e., electrodes, catalysts, permanent magnets, and many more are considered highly promising for these and similar applications. Innovative synthesis techniques are developed, resulting in new compounds as well as known ones with unique struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 267 publications
0
20
0
Order By: Relevance
“…An appealing alternative to the arc- and RF-melting methods is microwave (MW) synthesis, , which has been proven effective for the preparation of intermetallics compounds, e.g., Ti 3 SiC 2 , MnFe 2 Si, and Mg 2 Sn . The MW heating provides for concentrated delivery of thermal energy to the metallic mixture . Such rapid heating, however, should be carefully controlled to avoid an implosion of the evacuated tube that encloses the crucible with the reactants.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An appealing alternative to the arc- and RF-melting methods is microwave (MW) synthesis, , which has been proven effective for the preparation of intermetallics compounds, e.g., Ti 3 SiC 2 , MnFe 2 Si, and Mg 2 Sn . The MW heating provides for concentrated delivery of thermal energy to the metallic mixture . Such rapid heating, however, should be carefully controlled to avoid an implosion of the evacuated tube that encloses the crucible with the reactants.…”
Section: Results and Discussionmentioning
confidence: 99%
“…31 The MW heating provides for concentrated delivery of thermal energy to the metallic mixture. 32 Such rapid heating, however, should be carefully controlled to avoid an implosion of the evacuated tube that encloses the crucible with the reactants. We found that adding glass wool above and below the alumina crucible provides sufficient heat insulation, making the quartz tube stable for a longer time.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The sustainable green synthesis and fabrication of functional solid-state materials and devices is an integral part of this process; energy consumption and environmental impact must be minimised as a priority. [1][2][3] For several decades now, the physics of microwaves (MWs) has inspired the creativity of synthetic chemists. 4,5 Correspondingly, MW synthesis routes have produced a myriad of inorganic solid materials with various structures and morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the major benefits of time/energy savings; rapid heating rates; fast throughput; precise, selective heating, and reduction of waste heat/hazardous chemicals have been delivered. [2][3][4][5][6][7][8][9][10][11] Nevertheless, MW synthesis still faces many challenges before its implementation as a primary route to advanced materials manufacturing could be considered. [2][3][4][5][6][7]10 The Mg 2 X (X = Si, Ge, Sn) family crystallises with the facecentered cubic, antifluorite structure (space group Fm-3m) in which Mg atoms occupy the 8c (1/4, 1/4, 1/4) interstitial sites within a CCP lattice of X atoms (4a sites; Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…The most efficient and widely used sintering technique for thermoelectric materials is spark plasma sintering (SPS) [ 11 ] using a pulsed DC current. However, for materials with high ion mobility, which include superionic compounds, this technique does not seem to be suitable due to possible ion migration, resulting in a change in chemical composition of such materials [ 12 ].…”
Section: Introductionmentioning
confidence: 99%